Dialogo sul pianeta. Intervista a Giuseppe Genna e Pino Tripodi (Itinera, 2023)
Giuseppe Genna, author of Grande Madre Rossa (Mondadori 2004), Dies Irae (Rizzoli 2006), Hitler (Mondadori 2008) and Reality. Cosa è successo (Rizzoli 2020) among others, is one of the most important contemporary Italian writers. Pino Tripodi, author of Settesette. Una rivoluzione. La vita (Milieu Edizioni 2012) and Per sempre partigiano. L’insurrezione di Santa Libera (DeriveApprodi 2016) among others, has been a protagonist of the Italian Movimento del ’77. The book Pianetica (2022) was born from their collaboration as part of a wider project of planetary literature. We have asked the two authors to introduce us in this literary event.
Keywords: Gaia, Anthropocene, Cartography, Globe, Latour